Christian Doctrine and Biological Mutualism: Some Explorations in Systematic and Philosophical Theology. Issue 2 (2nd April 2020) - Davison, Andrew
ABSTRACT: Theologians are familiar with competitive relationships between organisms. Biology, however, also presents us with organisms engaged in mutually supportive relationships, in a pattern both widespread and often crucial for survival. This paper considers some of the challenges to traditional accounts of Christian doctrine—principally to creation, Christology and eschatology—posed by biological mutualism, especially in the phenomenon of compound organisms, composed of cells from more than one species. It also suggests ways in which theological traditions preserve philosophical resources that can be of use in thinking theologically about inter-organism relationships, and to philosophical discussions of biological mutualism more generally.